Clinical relevance and inter-test reliability of anti-infliximab antibodies and infliximab trough levels in patients with inflammatory bowel disease. Issue 2 (February 2016) - Guiotto, Cristina; Daperno, Marco; Frigerio, Francesco; Vizzini, Margherita; Cerruti, Roberta; Ercole, Elena; Cosimato, Maurizio; Lavagna, Alessandro; Germano, Laura; Migliardi, Marco; Rocca, Rodolfo
Abstract: Background: Treatment with infliximab is a common option for inflammatory bowel disease (IBD) patients. Therapeutic drug monitoring could improve treatment management. Aims: To test inter-test reliability of two commercially available diagnostic kits for infliximab trough levels and infliximab antibodies, and their association with treatment outcomes. Methods: 86 IBD outpatients on infliximab maintenance treatment were enrolled in a prospective cross-sectional study, 115 samples were available for inter-test reliability. Results: Inter-test agreement was good both for trough levels (concordance correlation coefficient 0.78, weighted κ 0.60, Sperman's ρ 0.937) and for infliximab antibodies (weighted κ 0.79) measurement, when comparing Promonitor and ImmunDiagnostik kits. According to manufacturers' cut-off values, trough levels were classified as undetectable (17%), low (21%) or in range (63%). The only significant associations were: mucosal healing ( p = 0.026; OR 6.50), infliximab antibody status ( p = 0.0015; OR 0.031) and adverse events ( p = 0.009; OR 0.115). Higher trough levels were observed among patients on concomitant steroid/immunosuppressive therapy and among patients with dose-intensification. Infliximab antibodies were significantly associated to treatment-related adverse events ( p = 0.0003, OR 30.42), and to lower trough levels, but not to other clinical variables. Conclusion: The two tests performed equally well. Infliximab antibodies were associated to adverse events, while trough levels were not associated to treatment outcomes.